Diseases in tobacco with monoculture and polyculture farming systems - Januarsih, Vera; Khairani, Hagia Sophia; Damayanti, Tri Asmira (Agrovigor, 2025)
Tobacco (Nicotiana tabacum L.) is an important agricultural product in Indonesia. Disease information on tobacco is required to develop effective control methods for supporting a proper tobacco farming system. This study investigates the disease type and intensity of tobacco in monoculture and polyculture cropping systems in Patebon District, Kendal Regency, Central Java. Disease evaluation factors such as types of symptoms, disease incidence and severity, and crop productivity under both crop systems were measured on tobacco every week for four weeks from 14 to 17 weeks after planting, as well as during harvest. Microscopic observation was used to identify the causative infections. The findings revealed that the disease makeup differed amongst crop systems. The leaf curl (Tobacco leaf curl virus) and mosaic (Tobacco mosaic virus) diseases were discovered in both cropping systems. However, anthracnose (Colletotrichum sp.) and leaf spot (Cladosporium sp.) were only observed in monoculture farming systems, whereas wildfire (Pseudomonas syringae pv. tabaci) was only identified in polyculture farming systems at a low incidence. In general, disease incidence and severity were higher in monoculture agriculture systems than in polyculture crops. Furthermore, the policulture crop system had a slightly higher yield, indicating that tobacco would be better planted in polyculture than monoculture crop systems.